Layanan Konseling Individual Dengan Pendekatan Rational Emotif Behaviour Therapy Untuk Meningkatkan Self-Esteem Siswa di SMA Kristen 1 Tomohon - Mansur, Djailan (Peneliti.net, 2024)
Rational Emotive Behavior Therapy to improve students' self-esteem is a guidance and counseling service that aims to change a person's irrational views and beliefs into rational ones. This research aims to look at individual counseling services using a rational emotive behavior approach for students at SMA Kristen 1 Tomohon. Students with low self-esteem were found, such as being alone, not liking socializing, and being bullied. The problem examined in this research uses guidance and counseling action research (PTBK). The target subjects of this research were class XII students of SMA Kristen 1 Tomohon. The data collection instruments were the researchers themselves using observation techniques, interviews, checklists and document analysis. The data was analyzed using qualitative analysis. This research took place in 2 cycles and the results can be concluded that individual counseling services using a rational emotive behavior therapy approach can increase students' self-esteem.